Complex Regional Pain Syndrome (CPRS): A Literature Review - Ini Hidayat Makbul; Kadek Nandita Nugraha; Afif Farras; Baiq Inna Dwi Hardyningrat; Devi Chandra Kirana; Najla Aulia Yahya; Salsabila Dinda Nuril Ishlahi; Siti Nurhaliza; Shofia Kadarisma; Yunita Hapsari; Amanullah, Mohammad Sany Rosafi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
CRPS (Complex Regional Pain Syndrome) occurs due to tissue trauma, leading to inflammation, activation of peripheral nociceptors, and increased regulation of neuronal processes. The etiology of CRPS is not fully understood, but it is believed to be related to an inappropriate inflammatory response and dysfunction in the central and peripheral nervous systems. The purpose of this article is to provide additional information regarding CRPS, thereby facilitating more accurate diagnosis and effective treatment. The research method used is a literature review, which discusses the definition, etiology, epidemiology, pathophysiology, diagnosis, and management of Complex Regional Pain Syndrome (CRPS), drawing on sources from PubMed, ProQuest, ScienceDirect, and Google Scholar. Future research is essential to deepen the understanding of this syndrome and create opportunities for more effective prevention and treatment of CRPS.